EU import measures and the developing countries - Marc Auboin; Sam Laird (World Trade Organization (WTO), 1998)
The EU's import policies towards developing countries are complex, stemming from important sectoral and country variations in policy. Average tariffs are modest, and, while there are tariff peaks and escalation in some areas of interest to developing countries, these are being reduced as a result of the implementation of the results of the Uruguay Round. The use of non-tariff measures has fallen, particularly as a result of agricultural tariffication, and is being further reduced in textiles and clothing. The elimination of VERs has not led to an increase in the use of alternative measures. Contingency protection falls more heavily in chemicals, iron and steel, certain textile items and certain electrical consumer goods and on Asian, Central and Eastern European and former Soviet Union countries. The operation of various factors appears to be working to mitigate the use of trade defence measures in recent years, helping to counter pressures that seem likely to arise as liberalization proceeds.
Keywords: F13; 330; European Union; trade policy; developing countries